2013
DOI: 10.1080/02615479.2012.705273
|View full text |Cite
|
Sign up to set email alerts
|

‘Not Easily Put Into a Box’: Constructing Professional Identity

Abstract: 'Not easily put into a box': constructing professional identityResearching the interplay between social work students' personal and professional identities, I found that, in talking about becoming professionals, students drew on a wide range of discourses. Three common usages of the term 'professional identity' are explored: it can be thought of in relation to desired traits; it can also be used in a collective sense to convey the 'identity of the profession'. Taking a more subjective approach, professional id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 19 publications
1
55
0
3
Order By: Relevance
“…Through this 120 G. Kirwan and C. Mc Guckin process members of the profession identify with others in their collective and thus acquire an individual and group professional identity. As Wiles (2012) discovered from her research, definitions of the term professional identity may vary but more easily identified will be commonly held understandings within any profession of the traits associated with membership of that particular profession. Measures of professional competence and readiness to become a full member of a profession usually require the individual to display attainment of an agreed level of skills, knowledge, and values, which have been assimilated during the educational process.…”
Section: Professionalismmentioning
confidence: 96%
“…Through this 120 G. Kirwan and C. Mc Guckin process members of the profession identify with others in their collective and thus acquire an individual and group professional identity. As Wiles (2012) discovered from her research, definitions of the term professional identity may vary but more easily identified will be commonly held understandings within any profession of the traits associated with membership of that particular profession. Measures of professional competence and readiness to become a full member of a profession usually require the individual to display attainment of an agreed level of skills, knowledge, and values, which have been assimilated during the educational process.…”
Section: Professionalismmentioning
confidence: 96%
“…Cross-section research design is not uncommon in this research area. In the recent literature, cross-sectional research design has been employed to study professional identity construction among final year students (Smith et al, 2014;Wiles, 2013). In addition the present study was conducted over a period of six months and we have interviewed the students multiple times to ensure the validity of emerging categories.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…The focus on students' professional development experiences and the role of their stories in making sense of educational realities can become crucial for broadening or reconceptualising the languages of professional identity (Wiles, 2013). Social work training, as with healthcare training, shapes the values and pattern of practice for social work professionals.…”
Section: Assessing Interprofessional Competencies?mentioning
confidence: 99%